Pemanfaatan Aplikasi ChatGPT dalam Meningkatkan Kemampuan Mahasiswa pada Mata Kuliah Maharoh Kitabah - Bakhrum Amir (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2024)
This study examines the utilization of the ChatGPT application in enhancing students' writing skills in the Maharoh Kitabah course for the fifth-semester students of the Arabic Language Education program at IAIQI Indralaya, focusing on the development of grammar, vocabulary, and sentence structure competencies. The urgency of this research stems from the limited studies on the integration of artificial intelligence technology in Arabic language learning, particularly within the context of higher education in Indonesia. Employing a qualitative approach with a case study design, the study involved 11 fifth-semester students from the Arabic Language Education program at the Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya. Data collection was conducted through a combination of participatory observation, semi-structured interviews, document analysis, and questionnaires, analyzed using thematic analysis with triangulation validation. The results revealed a significant improvement in students' writing abilities, with a 20% increase in grammar mastery, 22% in vocabulary acquisition, and 18% in sentence structure. ChatGPT proved effective in providing real-time feedback and facilitating self-directed learning. Based on these findings, the study offers strategic recommendations for integrating AI-based tools into Arabic language learning curricula, emphasizing the development of a balanced learning framework between technology utilization and conventional methods. Keywords: ChatGPT, Maharoh Kitabah, Arabic language learning, educational technology, writing skills